The attention of the scholars of Sulaimani to the hadith: Sheikh Mohammed Khal for example - احمد, پ. ی. د. ئاسۆ رضا (Sulaimani Journal for Humanities, 2023)
This study focuses on a scientific aspect of Sheikh Khal, namely his attention to the hadiths of the Prophet (peace be upon him) in his writings as evidence or interpretation of Qur'anic verses or for any other purpose. Dispelling the doubts of some who believe that Kurdish scholars have not paid enough attention to the hadiths of the Prophet (peace be upon him) compared to other sciences such as jurisprudence, interpretation and interpretation.